(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This work aims to study the effect of using fiber wire mesh on the flexural and shear properties of RC concrete beams. Six reinforced concrete beams (120*180*1220mm) were tested under two load points. Fiber wire mesh was applied with two manners, first one is three layers as U shape around the section of the beam, the second one is four layers around overall section of beam. The test results indicated that using of fiber wire mesh as additional reinforcement can increase the ultimate load of about (1.85-3.58% in the case of flexural) and (17.7-23.7% in case of shear). Also, results showed that an increasing in first cracking load is obtained from (42.8-85.7% in case of flexural) and from (41.2-76.5% in case of shear). Also the shear behavior of beams becomes more ductile when the fiber wire mesh was used in beams. The cracks of shrinkage was disappeared when the fiber wire mesh surround the section of the beam.